Study on the Law of Rock Anelastic Recovery and the Characteristics of In Situ Stress Field of 2000 m Deep Stratum in Metal Mines of Coastal Area - Yuezheng Zhang; Hongguang Ji; Hanhua Xu (Advances in Materials Science and Engineering)
In situ stress field in deep strata is dominated by self-weight stress and tectonic stress, which is the dynamic source of a series of mining dynamic disasters such as rock burst, mine earthquake, and collapse. To develop deep resources and build deep engineering construction, the distribution characteristics of the in situ stress field must first be ascertained, so as to provide a basic basis for the engineering surrounding rock support design and disaster risk prevention and control. In this paper, taking the Sanshandao Gold Mine in the coastal area as the engineering background, in the early stage of the construction of the 2000 m deep shaft, the anelastic strain recovery method was used to measure the deep in situ stress field. The laws and characteristics of hysteretic elastic recovery of rock at different depths are obtained through experiments, and the effects of temperature, time, and other factors on strain recovery are revealed. The in situ stress test results are basically consistent with the traditional test methods. This method has low operational complexity and better application effect in deep formations. The research has accumulated test experience and basis for carrying out in situ stress measurement in the range of 2000 m and even deeper.